2011
DOI: 10.1007/s00216-011-4945-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue method to quantify pesticides in fish muscle by QuEChERS-based extraction and LC-MS/MS

Abstract: Pesticide residues in fish muscle are an environmental and a health safety concern which requires analytical methods presenting high sensitivity and low limits of quantification. In this study, adapted QuEChERS method, coupled to liquid chromatography tandem mass spectrometry (Scheduled MRM-5500 QTRAP), was developed to quantify 13 pesticides (azoxystrobin, clomazone, diflufenican, dimethachlor, carbendazim, iprodion, isoproturon, mesosulfuron-methyl, metazachlor, napropamid, quizalofop and thifensulfuron-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 31 publications
3
33
0
1
Order By: Relevance
“…In the analysis of pesticide residues in food, the quadrupole-linear ion trap tandem mass spectrometer has been used mainly to analyze pesticide residues in vegetables and fruit (Sinha et al 2012;Afify et al 2010;Lee et al 2009a, b;Pihlstrom et al 2007;Banerjee et al 2007), (Lee et al 2009a, b), cocoa beans (Zainudin et al 2015), lavandin oil (Fillatre et al 2014) fruit beverages (Tran et al 2012;Ferrer et al 2011), and fish muscle (Lazartigues et al 2011). …”
Section: Quadrupole-linear Ion Trap Tandem Mass Spectrometermentioning
confidence: 99%
“…In the analysis of pesticide residues in food, the quadrupole-linear ion trap tandem mass spectrometer has been used mainly to analyze pesticide residues in vegetables and fruit (Sinha et al 2012;Afify et al 2010;Lee et al 2009a, b;Pihlstrom et al 2007;Banerjee et al 2007), (Lee et al 2009a, b), cocoa beans (Zainudin et al 2015), lavandin oil (Fillatre et al 2014) fruit beverages (Tran et al 2012;Ferrer et al 2011), and fish muscle (Lazartigues et al 2011). …”
Section: Quadrupole-linear Ion Trap Tandem Mass Spectrometermentioning
confidence: 99%
“…Several authors have reported good results after using this high-sensitive instrument, allowing the simultaneous identification and quantification of the proteins of interest (Grobosch et al, 2012;Janeckova et al, 2012;Lazartigues et al, 2011;Li et al, 2011;Paine et al, 2012;Rust et al, 2012;Wu et al, 2011).…”
Section: Ab Sciex Qtrap R 5500 Lc/ms/ms Systemmentioning
confidence: 99%
“…Enhancement effects were found for most of the carbamate pesticides in matrix (Nos. 3,7,9,11,14,18,21,22,25,27,33,42,60, 65, 69, 108, 136, Table 3). The repetitions were also good (RSDs below 15%) and the online GPC-GC/MS method was suitable to measure these pesticides if calibrated by matrix-matched standards.…”
Section: Matrix Enhancement Effects Measured By Online Gpc-gc/msmentioning
confidence: 99%
“…Extensive sample preparation methods were reported to remove interference before measurement, such as solid-phase extraction (SPE), [2,[4][5][6][7] gel permeation chromatography (GPC) [5,[8][9][10][11] and the quick, easy, cheap, effective, rugged and safe sample preparation method (QuEChERS protocol, a method derived from the dispersive SPE with the use of primary secondary amine (PSA) as sorbent). [5,[12][13][14][15][16][17] Buffering QuEChERS methods were developed to improve the recoveries of pH-dependent pesticides. [18][19][20][21][22][23] Analyte protectants were applied to block the active sites in the instruments.…”
mentioning
confidence: 99%